2021
DOI: 10.3390/plasma4010009
|View full text |Cite
|
Sign up to set email alerts
|

Progresses on the Use of Two-Photon Absorption Laser Induced Fluorescence (TALIF) Diagnostics for Measuring Absolute Atomic Densities in Plasmas and Flames

Abstract: Recent developments in plasma science and technology have opened new areas of research both for fundamental purposes (e.g., description of key physical phenomena involved in laboratory plasmas) and novel applications (material synthesis, microelectronics, thin film deposition, biomedicine, environment, flow control, to name a few). With the increasing availability of advanced optical diagnostics (fast framing imaging, gas flow visualization, emission/absorption spectroscopy, etc.), a better understanding of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 109 publications
0
21
0
Order By: Relevance
“…(c) TALIF spectroscopy for measuring absolute atomic densities in the plasma discharge. Reproduced with permission from ref . Copyright [2021] [MDPI].…”
Section: Adapting Current Sensors For Monitoring the Plasma–biologica...mentioning
confidence: 99%
“…(c) TALIF spectroscopy for measuring absolute atomic densities in the plasma discharge. Reproduced with permission from ref . Copyright [2021] [MDPI].…”
Section: Adapting Current Sensors For Monitoring the Plasma–biologica...mentioning
confidence: 99%
“…Figure 11b Each discharge cycle can be divided into Phase Ⅰ and Phase Ⅱ. As can be seen from Figure 13a, in Phase Ⅰ, the O atoms are mainly produced by the dissociation of Reactions ( 6) and (7) and are consumed by Reactions ( 8) and (12). According to Figure 13b, in Phase Ⅱ, (10), ( 11), ( 13), ( 14) are the main consumption reactions.…”
Section: O-talif Measurement and Calibrationmentioning
confidence: 99%
“…[6] Studies have shown that RONS play an important role in etching organic films, surface treatments, plasma medicine, and so on. [7][8][9] Among them, atomic oxygen is a powerful oxidant and is considered essential in many plasma biomedical applications. [10] As an active diagnostic technique, two-photon laser-induced fluorescence (TALIF) enables the diagnostics of the spatially and temporally resolved absolute concentration of O atoms with minimal impact on the NAPP.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, TALIF measurements are difficult in conditions where the fluorescence lifetime is shorter than the laser pulse duration. In this case, the use of picosecond or femtosecond lasers can be a better solution 27,36,37 .…”
Section: Fluorescence Lifetime and Quenching Ratementioning
confidence: 99%